Economic Contributions of Agriculture, Natural Resources, and Related Industries in Florida in 2009 - Alan W. Hodges; Mohammad Rahmani; Thomas J. Stevens (EDIS)
Agriculture, natural resources, and related industries are a significant force in the economy of Florida. It is important to recognize the extent of their economic contributions for informed public policy. IFAS economists Alan W. Hodges, Mohammad Rahmani, and Thomas J. Stevens prepared this 19-page analysis using the IMPLAN regional economic modeling system and associated state and county databases. The economic contributions of these industries were evaluated for 2009 to update previous reports and provide further information on economic trends in the wake of the historic global recession of 2007-2009. Published by the UF Department of Food and Resource Economics, August 2011. (UF/IFAS photo by Thomas Wright)